(资料图)
1、平方和公式n(n+1)(2n+1)/6 即1^2+2^2+3^2+…+n^2=n(n+1)(2n+1)/6 (注:N^2=N的平方) 证明1+4+9+…+n^2=N(N+1)(2N+1)/6 证法一(归纳猜想法): N=1时,1=1(1+1)(2×1+1)/6=1 2、N=2时,1+4=2(2+1)(2×2+1)/6=5 3、设N=x时。
2、公式成立,即1+4+9+…+x2=x(x+1)(2x+1)/6 则当N=x+1时, 1+4+9+…+x2+(x+1)2=x(x+1)(2x+1)/6+(x+1)2 =(x+1)[2(x2)+x+6(x+1)]/6 =(x+1)[2(x2)+7x+6]/6 =(x+1)(2x+3)(x+2)/6 =(x+1)[(x+1)+1][2(x+1)+1]/6 综上所述。
3、平方和公式1^2+2^2+3^2+…+n^2=n(n+1)(2n+1)/6成立,得证。
本文就为大家分享到这里,希望小伙伴们会喜欢。
Copyright 2015-2022 财报分析网版权所有 备案号:京ICP备12018864号-25 联系邮箱:29 13 23 6 @qq.com